Bertrand Russell and Alfred North Whitehead: On “Common” Experiences Shaping Different Visions of Philosophy - Gutowski, Piotr (Roczniki Filozoficzne, 2024)
In the article I address the relationship between the nature of Whitehead’s and Russell’s philosophy and the intense transformative experiences of these thinkers caused by certain individual events. For Russell, such an intense experience was that triggered by a powerful pain attack of Whitehead’s wife Evelyn., in February 1901. The incident also involved Whitehead’s 2.5-year-old son Eric. Russell claims to have experienced a kind of mystical illumination at the time, which, in the space of about five minutes, completely changed his previous way of thinking: among other things, it equipped his atheism with the imperative to oppose everything that causes human suffering, especially the suffering of children, and led him to uncompromising pacifism. For Whitehead, who was reticent in revealing his experiences, a similar experience was the death of 18-year-old Eric at the end of World War I. According to Russell, it contributed to Whitehead’s abandonment of mathematics in favor of philosophy and to a renewed acceptance of the theism he had previously abandoned. I argue that Russell’s hypothesis is not unfounded, and try to make it more specific by pointing out that Whitehead found the consolation he sought in the concept of God preserving in memory the entire past and in the idea of the co-constitution of divine life by actual occasions. Of course, both the changes in Russell’s philosophy and the genesis of Whitehead’s philosophy can be explained otherwise than by reference to their individual intense experiences, for example, as the result of an argument that takes into account the current state of philosophical, scientific, moral and religious knowledge. Intuition tells us, however, that without taking into account the influence of these individual intensive experiences, their philosophical ideas would probably have a different character.